2004
DOI: 10.1029/2004gb002281
|View full text |Cite
|
Sign up to set email alerts
|

How soil moisture, rain pulses, and growth alter the response of ecosystem respiration to temperature

Abstract: [1] In this paper, we analyzed 3 years of carbon flux data from continuous eddy covariance measurements to investigate how soil moisture, rain pulses, and growth alter the response of ecosystem respiration to temperature. The data were acquired over an annual grassland and from the grass understory of an oak/grass savanna ecosystem in California. We observed that ecosystem respiration was an exponential function of soil temperature during the winter wet season and a jump in ecosystem respiration occurred, at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
334
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(368 citation statements)
references
References 58 publications
28
334
2
4
Order By: Relevance
“…In Rull soil, as in many semiarid locations, soil moisture strongly influences the physiological activity of vegetation and soil microbes (Qi and Xu, 2001) and thus the driest periods show the minor soil CO2 concentrations. Specially during the dry season and considering these semiarid environments, rain events cause a notable increase in the soil respiration (Xu et al, 2004;Chen et al, 2014). Xu et al (2004) confirmed that during dry seasons soil microbes respond quickly to a sudden increase in soil moisture from occasional rain events, and this is the cause of the great and anomalous increase in soil CO2 that took place in November 2015.…”
Section: Temporally Pattern Of Co2 Concentration In Soilmentioning
confidence: 86%
See 3 more Smart Citations
“…In Rull soil, as in many semiarid locations, soil moisture strongly influences the physiological activity of vegetation and soil microbes (Qi and Xu, 2001) and thus the driest periods show the minor soil CO2 concentrations. Specially during the dry season and considering these semiarid environments, rain events cause a notable increase in the soil respiration (Xu et al, 2004;Chen et al, 2014). Xu et al (2004) confirmed that during dry seasons soil microbes respond quickly to a sudden increase in soil moisture from occasional rain events, and this is the cause of the great and anomalous increase in soil CO2 that took place in November 2015.…”
Section: Temporally Pattern Of Co2 Concentration In Soilmentioning
confidence: 86%
“…Specially during the dry season and considering these semiarid environments, rain events cause a notable increase in the soil respiration (Xu et al, 2004;Chen et al, 2014). Xu et al (2004) confirmed that during dry seasons soil microbes respond quickly to a sudden increase in soil moisture from occasional rain events, and this is the cause of the great and anomalous increase in soil CO2 that took place in November 2015. Relative to this, Zornoza et al (2016) affirmed that intense precipitation events provoke soil saturation by water, which leads to decreases in soil respiration rates.…”
Section: Temporally Pattern Of Co2 Concentration In Soilmentioning
confidence: 86%
See 2 more Smart Citations
“…Es lógico que los valores más altos de respiración del suelo se hayan registrado en primavera, dado que la actividad biológica del suelo es máxima durante esta estación (Guidolotti et al 2013;Xu et al 2004), debido a las temperaturas templadas y a la disponibilidad de agua por las lluvias.…”
Section: Discussionunclassified